Active knee joint flexibility and sports activity - Hahn,T.; Foldspang, A.; Vestergaard, E.; Ingemann-Hansen,T. (Scandinavian Journal of Medicine & Science in Sports, 1999)
The aim of the study was to estimate active knee flexion and active knee extension in athletes and to investigate the potential association of each to different types of sports activity. Active knee extension and active knee flexion was measured in 339 athletes. Active knee extension was significantly higher in women than in men and significantly positively associated with weekly hours of swimming and weekly hours of competitive gymnastics. Active knee flexion was significantly positively associated with participation in basketball, and significantly negatively associated with age and weekly hours of soccer, European team handball and swimming. The results point to sport-specific adaptation of active knee flexion and active knee extension.